If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3.5 = 6.7 Reorder the terms: 3.5 + 6x = 6.7 Solving 3.5 + 6x = 6.7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + 6x = 6.7 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + 6x = 6.7 + -3.5 6x = 6.7 + -3.5 Combine like terms: 6.7 + -3.5 = 3.2 6x = 3.2 Divide each side by '6'. x = 0.5333333333 Simplifying x = 0.5333333333
| 4u+8v=-3v+2u | | 10x-1=4x+41 | | 87/y-10=19 | | 6(t+3)=45 | | x-72.5=28.4 | | 6y+12=7y+2 | | 5(n-2)=22 | | 3y=5x-18 | | 3/9*2/5 | | (2-2^3/2)^2= | | 8-7x-3=-59+4x-13 | | 5(x)-20=60 | | http://www.geteasysolution.com/1a-15=4a-3 | | (5x-9)+(10x+10)= | | 8x-6=4x+38 | | 5s-26=59 | | 3y=5x+18 | | y(3y+11)=4 | | 4s+27=91 | | y(3y+11)=11 | | 4y+16=6y+2 | | 10=s/7-1 | | x-3=17.5 | | 6(X-2)+10=6X-1 | | 5(x-7)+31=5X-4 | | -8(9-10)/2= | | -16+80=-160 | | .5(x-60)=25+6x | | x+7=2x+54 | | 2x+3y=4z+250 | | X+(X*.42)=27079 | | -16-80=-160 |